Bond strength of fly ash geopolymer with CFRP fabric after exposure to high temperature - Sarker, Prabir; Borak, A.; Mukherjee, A.; Rangan, V. (SMAR 2017, 2017)
ABSTRACT: This paper presents a study on the bond strength of fly ash geopolymer as an alternative to epoxy bonding agent for carbon fibre reinforced polymer (CFRP) fabrics subjected to high temperature. CFRP fabrics of 300 mm bonded length were tested for bond strength by direct shear tests after three hours of exposure to elevated temperature at 100 oC, 200 oC and 400 oC. It was found that the bond strength of fly ash geopolymer was less than that of the epoxy bonding agent at room temperature. However, the bond strength of epoxy was completely lost by the exposure to heat at 200 oC, while the geopolymer retained its full bond strength up to the maximum testing temperature of 400 oC. This shows the superior bonding performance of geopolymer with CFRP fabrics as compared to that of conventional epoxy bonding agent when exposed to high temperature.